1993
DOI: 10.1073/pnas.90.10.4753
|View full text |Cite|
|
Sign up to set email alerts
|

Reverse gyrase: a helicase-like domain and a type I topoisomerase in the same polypeptide.

Abstract: Reverse gyrase is a type I DNA topoisomerase able to positively supercoil DNA and is found in thermophiic archaebacteria and eubacteria. The gene coding for this protein was cloned from Sulfolobus acidocaldarius DSM 639. Analysis of the 1247-amino acid sequence and comparison of it with available sequence data suggest that reverse gyrase is constituted of two distinct domains: (i) a C-terminal domain of -630 amino acids clearly related to eubacterial topoisomerase I (Escherichia coli topA and topB gene product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
105
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 34 publications
1
105
0
Order By: Relevance
“…Also encoded are four topoisomerases: one ATP-independent type I, homologous to TopA (Sso0907), and two ATP-dependent reverse gyrases (Sso0420 and Sso0963). One of the latter is closely related to TopR of S. acidocaldarius (46), whereas the other is nearly identical to TopR of S. shibatae (47). The genome contains only one type II topoisomerase of the TopoVI family (Sso0968 and Sso0969) (48).…”
Section: Dna Replication and The Cell Cyclementioning
confidence: 99%
“…Also encoded are four topoisomerases: one ATP-independent type I, homologous to TopA (Sso0907), and two ATP-dependent reverse gyrases (Sso0420 and Sso0963). One of the latter is closely related to TopR of S. acidocaldarius (46), whereas the other is nearly identical to TopR of S. shibatae (47). The genome contains only one type II topoisomerase of the TopoVI family (Sso0968 and Sso0969) (48).…”
Section: Dna Replication and The Cell Cyclementioning
confidence: 99%
“…Mechanistic studies showed that it is transiently linked to the DNA by a 5Ј phosphotyrosyl bond (22,24), classifying it in the type I 5Ј topoisomerase family as proposed by Roca (38). Sequence analysis further showed that it is a single polypeptide containing putative helicase and topoisomerase domains located in the amino-and carboxy-terminal, respectively, parts of the protein (9). The helicase domain exhibits motifs found in DNA and RNA helicases, and the topoisomerase domain exhibits a significant similarity with the 5Ј topoisomerase I (protein ) from Escherichia coli.…”
mentioning
confidence: 92%
“…In numerous DEAD box proteins, the helicase core provides the basic DEAD box protein functions, and large N-and/or C-terminal extensions (Figure 1) modulate the activity of the helicase core by conferring substrate specificity or by mediating contacts with interacting proteins (Schmid and Linder 1992; see 'Modulation of the helicase core activity by interacting partners and flanking domains'). In addition, the helicase core appears as a module in several enzymes involved in nucleic acid processing, such as DNA topoisomerases (Confalonieri et al, 1993;Rodriguez and Stock, 2002), restriction enzymes (Gorbalenya and Koonin, 1991;Szczelkun, 2000), chromatin remodeling enzymes (Flaus and Owen-Hughes, 2001), or Dicer (Ma et al, 2008).…”
Section: Introductionmentioning
confidence: 99%